Evaluation of counseling programs at junior high schools in Malang Regency during the covid-19 pandemic: Discrepancy model - Saputra, Nur Mega Aris; Wahyu, Riska; Rahman, Diniy Hidayatur (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
Counselors become adaptive individuals to changes that exist, even though they occur so quickly. One of them is that the COVID-19 pandemic has had an impact on the implementation of the counseling program in schools. The implementation of the counseling program in schools is expected to be able to accommodate the needs of students to be able to solve complex problems due to the COVID-19 pandemic. This research is evaluation research with a discrepancy evaluation model approach. The purpose of this study was to determine the implementation of the counseling program in schools based on predetermined standards. The implementation of this research is an evaluation with the research population being teacher guidance and counseling at the junior high school level in Malang Regency with a focus on implementing counseling programs during the COVID-19 pandemic. The research instrument is based on performance-based professional teacher evaluation guidelines on the third aspect of the fifth criterion. The data obtained were then analyzed descriptively and percentages to determine the implementation of the counseling program during the pandemic. The results show that counselors can adapt well to changes due to the covid-19 pandemic. This condition is indicated by the counselor starting to use technology in counseling (cybercounseling) to overcome the problems that occur so that they can carry out the program on a scheduled and limited basis in accordance with the health protocol rules. The follow-up results are recommendations to counselors for the implementation of future counseling programs.